Optimisation of [11C]-choline synthesis - Szydło, Marcin; Chmura, Agnieszka; Kowalski, Tomasz; Pocięgiel, Mateusz; d’Amico, Andrea; Sokół, Maria (Contemporary Oncology/Współczesna Onkologia, 2018)
The importance of [11C]-choline as a PET/CT marker has been extensively described, although its production presents considerable technical difficulties. The main ones are short half-lives and the occurrence of dimethylformamide (DMF) as a residual solvent. While the losses resulting from the radionuclide decay can be minimised by shortening the duration of the process, the best solution for reducing the content of DMF is its elimination from the reaction environment. In the current work two methods are compared for [11C]-choline synthesis – a green chemistry approach (with ethanol as a green solvent) and a dry synthesis. The results were compared with each other and with those of the method based on DMF. The solid phase synthesis proved to be the most effective in total elimination of DMF, its final release was the highest, and the synthesis time was the shortest. The optimised synthesis led to the formation of the desired radiotracer with a high radiochemical yield (65% ±3%) in a short production time (12 min) and the residual precursor in the final product at the level of 1 µg/ml. 27% increase of the saturation yield was possible, which resulted in 9 GBq higher activity from 40 minutes of beaming. Each test batch passed all standard quality control requirements, and the levels of residual DMEA were below the limits that have been published in the last Pharmacopoeia monograph